2016
DOI: 10.1016/j.ijcard.2015.09.076
|View full text |Cite
|
Sign up to set email alerts
|

Exploring quality of life in patients with and without heart failure

Abstract: (247 words)Aims: The EuroHeart Failure Survey Questionnaire (EHFSQ-1) has 39 questions on symptoms and quality of life (QoL); many items are related. We sought to identify underlying clusters amongst EHFSQ-1 questions, construct an overall "QoL score" and investigate its relationship to a single question asking patients to self-rate QoL. Methods and results:Factor analysis based on the principal component technique was used to identify patterns amongst responses to QoL questions from patients referred with sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…This study set out to explore the feasibility of implementing validated HR-QoL instruments in the routine heart failure clinic setting. 20,21 Besides NYHA class, our results demonstrated no biological factors that correlated with HR-QoL scores. The questionnaires were self-administered in the clinic waiting area prior to the medical consultation, for time efficiency and to reduce potential bias of opinion generated by interaction with clinical staff.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This study set out to explore the feasibility of implementing validated HR-QoL instruments in the routine heart failure clinic setting. 20,21 Besides NYHA class, our results demonstrated no biological factors that correlated with HR-QoL scores. The questionnaires were self-administered in the clinic waiting area prior to the medical consultation, for time efficiency and to reduce potential bias of opinion generated by interaction with clinical staff.…”
Section: Discussionmentioning
confidence: 51%
“…19 Additionally, the validation of single-item questions on selfreported health has been performed. 20,21 Besides NYHA class, our results demonstrated no biological factors that correlated with HR-QoL scores. As previously reported, left ventricular ejection fraction was not a predictor of HR-QoL.…”
Section: Discussionmentioning
confidence: 51%
“…Any depressive condition presented in HF patients alters their perception of QoL and affects the health status which, in turn, may negatively impact the patient’s self-care. Zhang et al showed that psychological distress, including stress, anxiety and depression, accounted for 13% of the variability of the overall QoL total score (the second of seven clusters of importance) [53].…”
Section: Discussionmentioning
confidence: 99%
“…or assessing well-being ("On a scale of 1-10 how well are you today? "); single questions are easy to administer and may be more efficient, although they may need to be interpreted in the context of the patients situation (for example, recent near-death experience, worsening heart failure or stable CHF) 17 . Indeed,…”
Section: Discussionmentioning
confidence: 99%